The Mounier-Kuhn syndrome - Milić Rade; Plavec Goran; Stojisavljević Marko; Tomić Ilija; Šarac Sanja (Vojnosanitetski Pregled)
Background. The Mounier-Kuhn syndrome (MKS) or tracheobronchomegaly (TBM) is a rare condition of unknown frequency, up to now about 100 cases have been reported. It presents by marked dilatation of the trachea and major bronchi, recurrent respiratory infections and consecutive bronchiectasis and scars in lung parenchyme. Sometimes enlargement of transversal colon may be present. Diagnosis is usually made radiologically. Cases report. We reviewed two patients 77 and 72 years old with typical clinical presentation and enlarged upper airways, in whom diagnosis of MKS was established by chest multislice computed tomography (MSCT). Transversal diameter of trachea was 30 mm in the first patient and 33 mm in the other one. Complications of syndrome (tracheal diverticulosis in the first patient, and pulmonary fibrosis, bulous emphysema and bronchiectasis in both patients) also were seen. Lung function tests showed mixed ventilation disorder, and disturbance of respiratory gases values in arterial blood samples. Conclusion. The Mounier-Kuhn syndrome is rare disorder, although diagnosis is often missed. Clinical presentation is similar to chronic obstructive pulmonary disease or bronchiectasis. Computed tomography is gold standard for diagnosis. Therapy is presumely supportive.